(untitled) (Journal of Informatics Education and Research, 2025)
The pursuit of transgender rights and social justice has emerged as a global movement which is aimed towards challenging the grounds and reasons of discrimination and focuses upon promoting inclusivity for individuals who identify as lesbian, gay, bisexual, transgender, queer, and other diverse sexual orientations and gender identities. This paper examines the facets of transgenders rights, the historical context, the challenges, and strategies for fostering inclusivity. Transgender rights demonstrates the pervasive history of violence, stigma, and marginalisation experienced by those who don’t fit into the binary notions of gender. This community has constantly faced discrimination and oppression. They have a long history behind the movements as the world witnesses today. Transgender groups have consistently fought back against structural oppression and demanded acknowledgment of their fundamental human rights, from the Stonewall Riots to the campaign for marriage equality. Nevertheless, many transgender individuals still endure violence, harassment, and discrimination because of their gender identity or sexual orientation, even in places where there has been tremendous progress. The idea of social justice, which places an emphasis on equality, justice, and dignity for all members of society, should be used to assimilate transgenders in the mainstream society.